FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA PERIODE TAHUN 2008-2010 (Students' Journal of Accounting and Banking, 2013)
This study aims to examine and analyze the influence of profitability, firm size, asset structure and ownership structure on capital structure. The population in this study is a manufacturing company listing on the JSE in the period 2008 to 2010. The samples obtained by using purposive sampling (based on criteria) obtained by 22 companies. Data were collected through observation method of secondary data. Then carried out a test method that includes the classic assumptions, hypothesis testing, the F test and t test, and analysis of the coefficient of determination (R2). To analyze the data using SPSS software version 16. Based on the results of the tests performed can be seen that the size of the company and the structure of assets a positive influence on the capital structure of the company, while profitability and ownership structure does not affect the capital structure of the company. The results of this study also found that profitability, firm size, asset structure and ownership structure affect together the capital structure. Keywords: profitability, firm size, asset structure, ownership structure and capital structure